Extramural German Activities and Motivation to Learn German as a Foreign Language in the Secondary Education Contex - Balázs Fajt (Studies in Self-Access Learning Journal)
This study investigates the motivation for learning German as a Foreign Language (GFL) of Hungarian secondary school students, in particular, their extramural activities and the impact of these activities on their learning motivation in second language (L2) acquisition. While much existing research on L2 learning motivation focuses on English, less attention is paid to other languages such as German, despite its economic and cultural importance in Hungary. Utilising Dörnyei’s (2005) L2 Motivational Self System framework, this paper explores how extramural German activities, such as interaction on social media, and consumption of German media, contribute to GFL learning motivation and GFL proficiency. Using the quantitative research paradigm, this paper analyses data collected from 546 Hungarian secondary school students assessing their motivation and the frequency of their engagement in different extramural German activities. The results indicate that these activities are generally pursued infrequently, however, certain types, particularly digital and interactive ones, have a positive effect on GFL learning motivation. Gender differences in frequency of engagement in extramural German activities were also found. The pedagogical implications of this paper suggest that the integration of certain extramural German activities into GFL learning may enhance learners’ motivation. The article also offers directions for future research to further explore the intricate dynamics of extramural activities and L2 learning motivation.